PEMBERIAN FORMULA BEBAS LAKTOSA UNTUK MENINGKATKAN STATUS GIZI ANAK USIA 6-24 BULAN YANG MENDERITA DIARE DI RSUD DATOE BINANGKANG KABUPATEN BOLAANG MONGONDOW - ., Mety; Mandey, Lucia C.; Mayulu, Nelly (Jurnal Ilmu dan Teknologi Pangan, 2013)
Diarrhea is the main reason of malnutrition, and furthemore inhibits infant growth. Malnutrition causes antibody declining on infant. In many cases, non-lactose formula and low lactose formula could accelerate diarrhea recovery, beside soy based formula and hydrolized protein. The objetives of this research were to compare the increasing weight then to determine and compare nutritional status on child by Z-score index based on age (Weight/Age) between non lactose formula group and low lactose formula group on diarrhea child at the age of 6-24 months. This research was using Quasi Eksperiment method, Pre and prost-test Control group desing.The results showed that after received non lactose formula, the average of patient weight became 9.30 Â± 2.0 kg. While in control group, the average of patient weight was 7.60 Â± 0.99 kg after treatment. The number of malnutrition patient on treatment group were 7 persons from 15 persons became no malnutrition patient, and on control group were 3 persons from 15 persons became 2 patients. It can be concluded that the increasing of child weight and nutritional status on non lactose formula group was better compared to low lactose formula group. Based on the results on the results of this research it can be recommended that diarrhrea child should be given non lactose formula beside breastmilk.